Exploración y práctica científica en México. El caso de Karl Theodor Sapper como geólogo oficial (1893-1896) - Morelos Rodríguez, Lucero (Jahrbuch für Geschichte Lateinamerikas, 2025)
Karl Theodor Sapper (1866-1945) was a prominent naturalist who was part of the constellation of German travelers, explorers and men of science who toured, described and studied portions of the American continent during the nineteenth century. The German geologist, geographer, ethnologist, Mayan and collector resided in Central America from 1888 to 1900; for twelve years he traveled from the Isthmus of Tehuantepec to Panama. In his travels through the tropics he made studies in geology, volcanology, mining, soils, linguistics, cartography, archaeology and economics, which are pioneers in the region. His initial activity as administrator of coffee farms in Alta Verapaz, Guatemala, -owned by his brother-, was combined with explorations and scientific studies, which ultimately reputed him worldwide fame as an expert scientific explorer of the Central American regions at the service of several of his governments and Mexico and as an epistemic authority in geology. In 1893 he signed a three-year contract with the Ministry of Development, Colonization, Industry and Commerce to perform the geological and geographical commission of Chiapas, Tabasco and the Yucatan Peninsula to perform the geological and geographical commission in charge of the Geological Institute of Mexico. The focus of this work is to study the geological practice at service of a government institution in Mexico by a transnational scientist like Sapper within the framework of “culture of exploration” proposed by Felix Driver, useful as a means of highlighting the ways in wich ideas, images and practices of exploration that crossed areas of culture during nineteenth century.